Implementation of Goal-Based Scenario Method in Speaking Courses - Dakhalan, Andi Muh.; Kuswandi, Dedi (Mau`izhah : Jurnal Kajian Keislaman, 2023)
The learning system in schools requires improvement, especially in the delivery of information and foreign language instruction. Goal-Based Scenario (GBS) is proposed as a solution to address the limitations of traditional learning by guiding students to learn content and skills to achieve learning objectives. The theoretical framework includes the development of GBS by Roger Schank and the Case-Based Reasoning theory that supports it. The benefits of GBS include better understanding, improved decision-making, risk understanding, and enhanced communication. This research emphasizes the importance of experience and cognitive conflict in learning, aligning with problem-based approaches and Gestalt psychology. The practical implications of applying GBS in speaking courses are significant, leading to increased motivation, student engagement, and practical skill development. Active, interactive, and contextual learning can be achieved through role-playing simulations, allowing students to face cognitive conflicts and problem-solving. The steps for implementing GBS in speaking courses include goal identification, mission, storyline development, role identification, scenario creation, resource provision, evaluation, feedback, and implementation, along with monitoring. In conclusion, the application of GBS in speaking courses yields benefits such as the development of communication skills in real-world contexts. GBS motivates students, enhances engagement, and provides an effective approach to foreign language instruction. This paper offers theoretical and practical foundations for the use of GBS in language learning contexts, particularly in speaking courses.